Investigating the Problems of Learning Arabic for Islamic Universities in the Era of Covid-19 Pandemic - Rahmawati, Rahmawati; Febriani, Suci Ramadhanti (International Journal of Language Education, 2021)
The 2019 Coronavirus pandemic (COVID-19) creates challenges for the Arabic learning process at Indonesian Islamic Universities, which is one of the mandatory subjects to support foreign language communication. This research aims to analyze the problems of learning Arabic online at UIN Imam Bonjol Padang in the situation of COVID-19. This research utilise case studies based on data includes observations of Arabic learning processes, collecting documentation through lesson plans and interviews with Arabic lecturers. The data analysis technique employs data triangulation through data collection, data reduction, data presentation, conclussion. The results ascertain that Arabic learning activities showed less effectiveness in COVID-19 situation, this was due to the varied problems ofÂ  learning Arabic based on online learning; the teacher's experience in designing online-based interactive media, the minimum stable learning platform, the minimal control process on students' language acquisition and supporting facilities in learning Arabic online. The findings of this study discover that Arabic lecturers to integrate all learning components holistically, so the Arabic learning process can achieve maximum results. This research recommends to the other research to find a solution to every problem that exists in Arabic learning in COVID-19 situation at UIN Imam Bonjol Padang.